(untitled) (Damascus University Journal of agriculture sciences, 2022)
This research was conducted at the Central Supply Laboratory and the Central Grain Laboratory, with the aim of studying the effect of adding some types of legumes flour on the physiochemical and rheological properties of locally produced wheat flour types. Two types of wheat flour (high-quality wheat flour and standard flour) and two types of legume flour (chickpea flour and lentil flour) were selected, and each type of wheat flour was fortified with (0, 5, 10 and 15%) with each type of legume flour, and the physiochemical and rheological tests were performed according to the methods approved in the AACC. The results of the physiochemical properties evaluation showed that there were significant differences between the mixtures, as moisture content and protein content decreased, while ash content and colour degree increased. Moreover, the addition of legume flour to wheat flour was associated with a quantitative and qualitative decrease in the gluten of the two types of wheat flour. On the other hand, the studied variables, wheat flour type, legume flour type and the addition ratio, showed significant effects on the farinograph properties, where the addition of legume flour to wheat flour significantly increased water absorption, dough development time and dough weakening degree, while dough stability time decreased. While the extensograph indicators showed a decrease in area, resistance to extension, maximum resistance to extension and elasticity, and increased extensibility, and therefore the results of the rheological characteristics evaluation indicated that fortifying locally produced wheat flour with different proportions of legume flour led to a decrease in the flour strength, and this entails adjustments in the manufacturing process when composite flour is used in the preparation of bakery products that require strong flours, such as bread and pasta. The results of measuring the fermentation power of wheat flour mixtures by measuring the volume of released CO2 showed that the addition of legume flour increased the fermentation power of wheat flour due to the increase in the proportion of simple sugars in the mixtures.